TILES-2019: A longitudinal physiologic and behavioral data set of medical residents in an intensive care unit - Yau, Joanna C.; Girault, Benjamin; Feng, Tiantian; Mundnich, Karel; Nadarajan, Amrutha; Booth, Brandon M.; Ferrara, Emilio; Lerman, Kristina; Hsieh, Eric; Narayanan, Shrikanth (Scientific Data, 2022)
The TILES-2019 data set consists of behavioral and physiological data gathered from 57 medical residents (i.e., trainees) working in an intensive care unit (ICU) in the United States. The data set allows for the exploration of longitudinal changes in well-being, teamwork, and job performance in a demanding environment, as residents worked in the ICU for three weeks. Residents wore a Fitbit, a Bluetooth-based proximity sensor, and an audio-feature recorder. They completed daily surveys and interviews at the beginning and end of their rotation. In addition, we collected data from environmental sensors (i.e., Internet-of-Things Bluetooth data hubs) and obtained hospital records (e.g., patient census) and residents’ job evaluations. This data set may be may be of interest to researchers interested in workplace stress, group dynamics, social support, the physical and psychological effects of witnessing patient deaths, predicting survey data from sensors, and privacy-aware and privacy-preserving machine learning. Notably, a small subset of the data was collected during the first wave of the COVID-19 pandemic. Measurement(s) Stress • Burnout • Affect • Depression • Sleep • Physical Activity Measurement • Alcohol Use History • Frequency Any Tobacco Use • Personality • Social Support • Intragroup Conflict • Challenge and Hindrance Stressors • Demographics • Context and Atypical Events • Daily Stressors • Most Stressful Event • Work Context • Job Performance • Job Satisfaction • Stressors at Work • Charting at Home • Coworker Trust • Social Networks at Work • Socialization Outside of Work • Use of Wellness Resources • Heart Rate • Step Count • Acoustic Features • Team Interactions • Proximity to Key Objects • Cell Phone Use • Hospital Contextual Data • Coping with Stress • Productivity at Work • Pride at Work • Teamwork • Support System Technology Type(s) Perceived Stress Scale - 14 Questionnaire • Survey • Patient Health Questionnaire - 9 Item • Pittsburgh Sleep Quality Index • FitBit • International Physical Activity Questionnaire (August 2002) Short Last 7 Days Self-Administered Format • Unihertz Atom Phone • Minew E8- TILES Interaction Sensors • Minew E8- Eddystone Beach • Rescuetime • Evaluations • Patient Census • Interview Sample Characteristic - Organism Homo sapiens Sample Characteristic - Location Los Angeles County and University of Southern California Medical Center